If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(3) + -3y = 15 Multiply 12 * 3 36 + -3y = 15 Solving 36 + -3y = 15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -3y = 15 + -36 Combine like terms: 36 + -36 = 0 0 + -3y = 15 + -36 -3y = 15 + -36 Combine like terms: 15 + -36 = -21 -3y = -21 Divide each side by '-3'. y = 7 Simplifying y = 7
| 4x+2y=58.80 | | 10x+3162+15x=3237 | | 9-(4-7*8)= | | X+(.2*X)=75.6 | | 20=100e^8y | | 4y-19=17 | | 5x/4-3/4=7/4 | | 67/2a-15 | | y=100e^8x | | (18)2+(x)2=(x+14) | | 21/.75 | | 7x^2+10=9 | | 5(x-4)=-3(x+2)+33 | | 0=x^2+14-45 | | 5x-3x+12=35-4x-9 | | M^2+15+56=0 | | 1+3lnx=0 | | 5(x-4)-3(x+2)=33 | | 48+6x=84 | | 19=7x+4x+8 | | 400=60p+4p^2 | | 18x^2+9=18 | | m=11/16 | | M+7+7=23+7 | | u/3=4.8 | | 5(x-14)+2x=5x | | 24/3^2/3 | | (x+5)(75-x)= | | 5/6=x/21 | | Y(a)=x(b) | | -1(-2)(-3)(-4)= | | 5x-(14+2x)=33 |